A framework for reform in the logistics and transportation sector: the case of the European Union accession - Ievsieieva, Kateryna (2012)
The European Union has pursued a regional development and enlargement policy aimed at the promotion of European interests while maintaining European stability. With an overall focus on regional cooperation, security, and stability, the EU enlargement strategy requires that countries, applying for EU membership, follow a strict development process that focuses on the establishment of a free market economy, democratic institutions of government, and a social system that provides for the health, welfare, and education of the country’s population. The aim of this paper is to study the major challenges in the field of transport in the European Union, as well as analysis of the measures taken within the framework of the transport policy of the European Union to address these problems during the accession process. The transport field is a headstone of the economy of Europe and essential for further economic development in the Union. However, the enlargements have complicated the variety of transport considerations. The Common Transport Policy for this moment is only one element created to cut down simulated difficulties by the EU in order to expand a transport policy. The European integration is one of the main priorities of the Ukrainian national policy. However, the transport system of Ukraine still does not meet the standards and requirements of the European Union and characterized by a substantial backlog with respect to infrastructure, equipment and regulations. Through an investigation East European regional policy of the European Union and Russian foreign policy vis-á-vis Ukraine, this paper will examine the interaction of international and internal interests in the field of transport.